Hypnotherapy in children with surgical pathology. - Yekhalov, V. V.; Yehorov, S. V.; Bahunina, O. A. (Medicni Perspektivi, 2018)
The article presents the data obtained during the examination of children with acute surgical pathology. The frequency of development, the severity of hyponatremia, and the effect of the syndrome of inadequate secretion of antidiuretic hormone on the development of hyponatremia have been established.